(3GdOQI GdoeVjFI ef NHQ SjO GdNdjbIs - (3CHh GdaVd eSYhO Hf eMeO LehY GdSLdeGSj GdaGSj, LehY,J (B1119 (3g` s
(3ChdgG (B:s
(3hHYO eGjLH Ydi GdeSde MaXg, hjLH Ydi Pi GdOjf eYQaJg GdcQjeI hSjQg hTeGFdg s
(3BNQgG (B:s
(3bGd LGeYg hcGf GdaQGZ efg YGe EKfJjf heGFI hCda hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B66 - (3U(B107s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B220 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B229s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B175 s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs